Technology and Operational Improvements in Tuyere Punching, Silencing, Pyrometry and Refractory Drilling Equipment - M. J. Marinigh (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
Increased safety requirements, higher operational costs, greater environmental restrictions, and new competitive processing techniques are the challenges smelter operators must confront in order to remain economically viable. In converting furnaces which have tuyeres such as the Noranda Reactor and the Teniente, Peirce Smith and Hoboken converters, efficient tuyere line management is critical to optimizing blowing rates, increasing refractory life, and improving safety. This paper will describe recent improvements made to equipment used for tuyere punching, tuyere silencing, tuyere pyrometry and refractory drilling of tuyeres and how the proper application of the equipment can lead to operational and safety improvements.